Otimização do processo de soldagem por fricção por ponto (FSpW) de soldas de materiais similares e dissimilares de ligas leves - Piccolo, Debora Regina Gastaldi (Universidade Federal de São Carlos, 2014)
Currently there is a lot of pressure in the aeronautical and automobilistic transport section in order to reduce the fuel consumption and consequently cost and gas emissions. This measure has increased in the last years the use of light alloys, as the alluminium s alloys and of more efficient methods for joining them. Nevertheless, there is some difficult in joining these alloys using the conventional methods. The Friction Spot Welding (FSpW) is a solid state joining technique, that has great advantages regarding others joining techniques, and therefore could be a viable alternative to replace the established technologies as Resistance Spot Welding (RSW) and riveting, which are widely used by the automotive industry. The present works aims to study, through the Friction Spot Welding process (FSpW), the similar welding conditions of AA5754-H111 aluminium alloy and also the dissimilar welds between AA5754-H111 aluminium alloy and AZ31-O magnesium alloy. The influence of process parameters over the microstructure and the mechanical properties of the welded joints, as well as, the optimization of the welding process were evaluated. The joints were produced in overlap configuration through a different combination of parameters, which were established by statistical methods for design of experiments, and later submitted to mechanical and metallurgical characterization. The results proved the feasibility of joining the similar and dissimilar plates of aluminium AA5754 and magnesium AZ31 through FSpW process. The similar joints showed great results of shear strength. However, in the dissimilar joints, the utilization of a zinc interlayer, in spite of leading to a great superficial finishing, didn t effectively decrease the amount of intermetallic compounds formed in the joint as it was expected, leading to low values of shear strength.
optimization of friction spot welding (FSpW) process of similar and dissimilar welds of light alloys
Keywords: Soldagem; FSpW; Ligas de alumínio; Ligas de magnésio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA